2020
DOI: 10.3892/ijmm.2020.4497
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone attenuates homocysteine‑induced apoptosis by regulating the connexin 43 pathway in H9C2 cells

Abstract: Pirfenidone (PFd) is an anti-fibrotic agent that is clinically used in the treatment of idiopathic pulmonary fibrosis. PFd has been shown to exert protective effects against damage to orbital fibroblasts, endothelial cells, liver cells and renal proximal tubular cells; however, its effect on myocardial cell apoptosis remains unclear. The present study aimed to characterize the effects of PFd on homocysteine (Hcy)-induced cardiomyocyte apoptosis and investigated the underlying mechanisms. H9c2 rat cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It has been shown that Fas-dependent alveolar apoptosis that results in inflammatory reaction and finally interstitial fibrosis is responsible for the battle against viruses and also responsible for sequels of infections such as Poxvirus, bacterial LPS, etc [35,47]. On the other hand, it has been shown that pirfenidone could decrease apoptosis [19,[48][49][50][51].…”
Section: Anti-apoptotic Effects Of Pirfenidonementioning
confidence: 99%
“…It has been shown that Fas-dependent alveolar apoptosis that results in inflammatory reaction and finally interstitial fibrosis is responsible for the battle against viruses and also responsible for sequels of infections such as Poxvirus, bacterial LPS, etc [35,47]. On the other hand, it has been shown that pirfenidone could decrease apoptosis [19,[48][49][50][51].…”
Section: Anti-apoptotic Effects Of Pirfenidonementioning
confidence: 99%
“…Furthermore, an Hcy-induced myocardial cell apoptosis was established in vitro . This model is widely used to study cardiomyocyte apoptosis ( Zhang et al, 2017 ; Aminzadeh & Mehrzadi, 2018 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant character of Pirfenidone suggests its capability for the treatment of hyperimmune response ( 3 , 24 ). Pirfenidone could decrease apoptosis and as a result combat sever viral inflammation, ARDS, and ARDS fibrosis ( 25 , 26 ). Finally, it has been demonstrated that Pirfenidone inhibits the AT1R/p38 MAPK pathway, decreases angiotensin II, and angiotensin II type 1 receptor, as well as angiotensin-converting enzyme (ACE) expression, which will both protect cells from developing fibrosis (LXR-α), and limit entrance of the COVID-19-SARS virus into cells by decreasing ACE receptors ( 2 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%